Inhaled nitric oxide mitigates need for extracorporeal membrane oxygenation in a patient with refractory acute hypoxemic respiratory failure due to cardiac and pulmonary shunts. (2018) - Nokes, Brandon; Yeneneh, Beeletsega; Maddux, Jake; Van Woerkom, Ryan C.; Lowell, Amelia; Callisen, Hannelisa; Patel, Bhavesh; Shamoun, Fadi; Fortuin, F. David; DeValeria, Patrick; Sen, Ayan
Abstract: We present a case of refractory acute hypoxemic respiratory failure due to influenza B pneumonia with concomitant large intra-atrial shunt (IAS) and severe pulmonary regurgitation in a patient with Saethre-Chotzen syndrome with prior pulmonary homograft placement. Our patient's hypoxemia improved with inhaled nitric oxide as an adjunct to mechanical ventilation without requiring extracorporeal membrane oxygenation, and eventually a percutaneous closure with a 30 mm CardioSeal patent foramen ovale closure device was accomplished. However, his peri-procedural hospital course was complicated by occluder device migration, which was retrieved with eventual surgical closure of the PFO. Nitric oxide has not demonstrated any statistically significant effect on mortality and only reported to transiently improved oxygenation in patients with hypoxemic respiratory failure. Our case demonstrates that inhaled nitric oxide may have a role in acute hypoxemic respiratory failure in a case with significant cardiac and pulmonary shunts.